THE USE OF PROJECT BASED LEARNING (PJBL) TO ENHANCE DESCRIPTIVE WRITING ABILITY OF EIGHTH GRADE STUDENTS AT MTS AL-HUDA GONDANG - Rahma Ika Fauziah; Anita Budi Rahayu (Universitas PGRI Mpu Sindok, 2025)
This study examines the application of Project-Based Learning (PjBL) to improve the descriptive writing ability of eighth-grade students at MTs Al-Huda Gondang, addressing identified difficulties in this skill. The research aimed to determine the significant difference in students' descriptive writing skills before and after being taught using the PjBL model. This study employed a pre-experimental design with a quantitative approach, using a one-group pretest-posttest design. The population was all eighth-grade students, with a sample of 20 students from class VIII-A selected through convenience sampling. Data analysis used a paired sample t-test. Results showed the average pretest score was 36 (Poor category) and the posttest score was 78 (Good category). The t-count (19.09) was greater than the t-table (1.725) at a 5% significance level with 19 degrees of freedom. Therefore, Hₐ was accepted, indicating a significant improvement in descriptive writing ability after implementing PjBL. It is concluded that the PjBL model effectively enhances the descriptive writing skills of eighth-grade students at MTs Al-Huda Gondang.